Burnout and Socio-demographic Characteristics of Nurses in Iran - Rashedi, Vahid; Rezaei, Mohammad; Gharib, Masoud (Galen Medical Journal, 2014)
Background: Nursing is considered as a profession at risk for high levels of stress and burnout, and these levels may be increasing as the care they deliver becomes complex. The purpose of this study was to investigate the relationship between burnout and socio-demographic characteristics of nurses.Materials and Methods: A cross-sectional descriptive-analytical design was used. The sample consisted of 194 nurses working in five hospitals of Hamadan University of Medical Sciences in Iran, who completed the Maslach Burnout Inventory (MBI) as well as a socio-demographic questionnaire. The data were analyzed using descriptive statistics, Pearson correlations, independent t-test and ANOVA.Results: Results indicated moderate levels of emotional exhaustion, depersonalization and low levels of personal accomplishment. There was significant relationship between burnout and age, length of employment, and educational level.Conclusion: Identifying an integrative process of burnout among nurses is an essential step in developing effective managerial strategies in order to address the problem. To prevent burnout, further research is necessary to determine the factors associated with it so that recommendations can be made for future wellness interventions. [GMJ. 2014;3(4):232-7]